Sistem Penyewaan Perlengkapan Tari dengan Menerapkan Sistem Pendukung Keputusan Berbasis Metode SAW (Studi Kasus: Sanggar Seni Pesona Wangka) - Ratu Bania, Naja; Pratama, M. Setya; Yang, Yang Agita Rindri (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Sanggar Pesona Wangka is a place for dance and music activities that have an important role in preserving Bangka Belitung culture. Sanggar Pesona Wangka also provides dance equipment rental. The process of renting dance equipment is still conducted conventionally so it takes longer. Another obstacle faced is the difficulty for tenants to obtain information regarding the availability of the dance equipment they need to rent. The conventional rent system is also considered inefficient because tenants must come to the studio to meet with the owner and directly select the dance equipment to be rented. This study aims to design and develop a website-based dance equipment rental system for Sanggar Pesona Wangka to facilitate the processing of the required data into accurate and easily accessible information for prospective tenants. The system implements a SAW (Simple Additive Weighting) method-based decision support system that can provide the best customer recommendations based on 2 criteria, namely the number of transactions and total transaction costs. Methods of data collection in this study using observation and interview methods. For system development using the prototype method with the programming language PHP and MySQL. System testing is implemented the black box testing and user acceptance testing methods. The test results show that the system runs 100% as expected. Meanwhile, from the results of user acceptance testing, it was obtained 92.6% percentage that conclude the system was feasible to use.